Analysis of Financial Statements to Measure the Financial Performance of PT. Unilever Indonesia Tbk. Period 2020-2022 - Mutiara Akbar Nasution; Lukas Destria Putra Ginting; Anisa Fitri; Nurdina Safitri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Analyzing financial statements is not only to find out whether a company's financial performance is good or bad; it can also be used to determine or build a strategy for future company planning. The type of research we use is descriptive-quantitative. The population and sample used in this study are the company's financial statements from PT. Unilever Indonesia Tbk. for the period 2020–2022. By using data analysis techniques that use indicators on each finance, it can be compared between one period and another. Finance PT. Unilever Indonesia Tbk. appears to fluctuate towards worsening due to the difficulty in paying both short-term and long-term liabilities.